THE IMPROVEMENT OF CPO QUALITY USING PHYSICAL PURIFICATION MATERIAL OF SHELL POWDER FOR RED COOKING OIL PRODUCTION - Usman, Muhammad; Julianti, Elisa; Elisabeth, Jenny (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2025)
The production of CPO (Crude Palm Oil) generated and utilized by the industry must consider market demand, prioritizing the quality of the final CPO product that complies with the SNI 01-2901-2021 standard. It includes free fatty acid (FFA) content, water, and impurities, with maximum limits of 5%, 0.25%, and 0.25%, respectively. Another parameter affecting CPO quality is the Deterioration of Bleachability Index (DOBI) value. This study investigates the potential use of calcium oxide (CaO) derived from seashells to improve CPO quality in the production of Red Cooking Oil (M3). The study design employed a Completely Randomized Design (CRD) with a non-factorial method. The treatment factor in this study was seashell powder heated at 600°C with varying concentrations: 0%, 1%, 2%, 3%, and 4%, as well as 1% Bleaching Earth commonly used at neutral pH (6-7 ). The treatments applied included K0 (no treatment), K1 (1% Bleaching Earth), K2 (1% Seashell Powder), K3 (2% Seashell Powder), K4 (3% Seashell Powder), and K5 (4% Seashell Powder) . The results showed that seashell powder significantly reduced free fatty acid content in K5 by 13.51%, decreased water content in K4 and K5 by 47.05%, and increased the DOBI value by 47.05%.